Reformas al Art. 380 del Código Orgánico Integral Penal para reducir el monto de los daños y que la multa tenga relación con la infracción - Azogue Gavilanez, Milton Gonzalo (2015)
Article 380 of the Code of Criminal Integral provides: "The person Materials.- damage as a result of a traffic accident caused property damage where the cost of repair is greater than two salaries and not exceeding six unified basic wage of the worker in general, it shall be punished with a fine of two unified basic wage of workers in general and reduction of six points on your driver's license, without prejudice to civil liability to third parties that is subject because of the infringement. In the case of the preceding paragraph, the person who drives a vehicle in the period in which the driver's license be suspended temporarily or permanently, shall be punished by a fine of five One worker in general basic salaries. The person following the accident caused only material damage whose repair cost exceeding six unified worker in general basic salaries shall be punished by a fine of four unified basic wage of workers in general and reduction of nine points on his license lead. In the case of the preceding paragraph, the person who drives a vehicle in the period in which the driver's license be suspended temporarily or permanently, will be fined seven unified workers' basic wages generally. In any case, the vehicle or the owner shall be jointly liable for civil damages ". It can be seen then that if there are accidents with less damage to US $ 700, will not be punished the offender, the penalty for such conduct as it is not provided. In the context of the statute invoked, it is clear that there is no relationship between the typical behavior and the fine imposed, imagine that a person causes damage to a vehicle for seven hundred dollars, then, should fix the vehicle, and shall also cancel the fine that is equal in quality, then in my opinion should be reduced even set fine for that offense. In this situation I decided to investigate this legal reality and base my proposal presented at the end of this thesis, which is that of reforming the Code of Criminal Integral